The Influence of Corporate Governance on Tax Avoidance and The Role of Independent Auditors in Vietnamese Firms - Hung, Pham Huy (Journal of Advances in Accounting, Economics, and Management, 2024)
This research addresses how corporate governance mechanisms influence tax avoidance in Vietnamese firms and the role of independent auditors in detecting or mitigating tax avoidance. The purpose of the research is to explore the relationship between corporate governance structures (e.g., independent boards, audit committees) and tax behavior, as well as to assess how auditors interact with these governance mechanisms to ensure tax compliance. A qualitative case study approach was used to analyze six companies from different sectors and governance models (2 state-owned enterprises; 2 family-owned private companies; and 2 publicly listed companies) through 18 interviews conducted between May 2024 and October 2024 with 3 key individuals from each company, including: Independent auditor; Company CEO; Manager or administrator, along with documentary analysis of financial statements and tax filings. The research found that firms with stronger governance (e.g., independent boards and active audit committees) are less likely to engage in tax avoidance, while weak governance structures often lead to more aggressive tax strategies. Independent auditors were more effective in well-governed firms, but faced ethical challenges in weaker ones. These findings are significant because they highlight the importance of strengthening governance frameworks and ensuring auditor independence to reduce tax avoidance and improve corporate transparency in Vietnam.